2017
DOI: 10.1038/s41467-017-01172-5
|View full text |Cite
|
Sign up to set email alerts
|

Sortilin limits EGFR signaling by promoting its internalization in lung cancer

Abstract: Tyrosine kinase receptors such as the epidermal growth factor receptor (EGFR) transduce information from the microenvironment into the cell and activate homeostatic signaling pathways. Internalization and degradation of EGFR after ligand binding limits the intensity of proliferative signaling, thereby helping to maintain cell integrity. In cancer cells, deregulation of EGFR trafficking has a variety of effects on tumor progression. Here we report that sortilin is a key regulator of EGFR internalization. Loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 64 publications
4
74
0
Order By: Relevance
“…NTSR3 or sortilin 1 has been implicated in the loading of EGFR into exosomes and sortilin depletion maintains EGFR on the cell surface, limiting EGFR endocytosis [19]. NTSR3 normally cycles between the cell membrane and the trans-Gogi network.…”
Section: Lung Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…NTSR3 or sortilin 1 has been implicated in the loading of EGFR into exosomes and sortilin depletion maintains EGFR on the cell surface, limiting EGFR endocytosis [19]. NTSR3 normally cycles between the cell membrane and the trans-Gogi network.…”
Section: Lung Cancermentioning
confidence: 99%
“…NTSR3 binds both stimulated and unstimulated EGFR, leading to its internalization. This eventually leads to EGFR expulsion via exosomes or in receptor degradation and hence signal termination [19]. Al-Akhrass et al found that low sortilin expression was associated with increased cellular proliferation and tumour growth, indicating that NTSR3 is a favorable prognostic marker in lung adenocarcinoma patients [19].…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Ligand-binding to RTKs triggers receptor internalisation and trafficking within the cells which determines strength, duration and spatial distribution of EGFR signals [7][8][9][10][11] . RTKs, including EGFRs are internalised through clathrin-dependent and -independent mechanisms, converging on the delivery of the receptors to early endosomes 7 .…”
Section: Introductionmentioning
confidence: 99%
“…(3) Tyrosine-protein kinase Mer (MERTK) was reported to be overexpressed in human non-small cell lung cancer [61]. (4) Sortilin (SORT) was reported as a regulator of EGFR intracellular trafficking, which in turn impacts lung tumor growth [62]. It was also reported that the silencing sortilin expression in tumor cells may introduce sortilin as a potential candidate for developing a novel targeted therapy in patients with ovarian carcinoma [63].…”
Section: Parallel Reaction Monitoring (Prm) Validationmentioning
confidence: 99%